2010
DOI: 10.1103/physreva.82.052313
|View full text |Cite
|
Sign up to set email alerts
|

Implementing quantum gates through scattering between a static and a flying qubit

Abstract: We investigate whether a two-qubit quantum gate can be implemented in a scattering process involving a flying and a static qubit. To this end, we focus on a paradigmatic setup made out of a mobile particle and a quantum impurity, whose respective spin degrees of freedom couple to each other during a one-dimensional scattering process. Once a condition for the occurrence of quantum gates is derived in terms of spin-dependent transmission coefficients, we show that this can be actually fulfilled through the inse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
(82 reference statements)
0
33
0
Order By: Relevance
“…are the projector operators associated with the singlet and triplet subspaces, respectively, of the f -SQ 1 system. Note that in the computational basis {|α f α 1 } (α f , α 1 =↑, ↓), a matrix element α f α 1 |R f 1 |α f α 1 yields the probability amplitude that, given the initial joint spin state |α f α 1 , f is reflected back and the final spin state is |α f α 1 [8,9] (an analogous statement holds forT f 1 ). Via the identities (4) and (5), one can easily verify that equation (7) immediately entails the proper normalization condition…”
Section: Read-out Of a Single Static Memory Qubitmentioning
confidence: 98%
See 1 more Smart Citation
“…are the projector operators associated with the singlet and triplet subspaces, respectively, of the f -SQ 1 system. Note that in the computational basis {|α f α 1 } (α f , α 1 =↑, ↓), a matrix element α f α 1 |R f 1 |α f α 1 yields the probability amplitude that, given the initial joint spin state |α f α 1 , f is reflected back and the final spin state is |α f α 1 [8,9] (an analogous statement holds forT f 1 ). Via the identities (4) and (5), one can easily verify that equation (7) immediately entails the proper normalization condition…”
Section: Read-out Of a Single Static Memory Qubitmentioning
confidence: 98%
“…Thereby, off-diagonal entries r 01 must vanish, which yields the condition r (m) s = e −2ikd 2 , i.e. kd 2 = π − arg[r (m) s (g)]/2 = h(kd 1 ), according to our definition of the h function (see above) 8 . By replacing this into equations (19) and (20), we immediately end up with r 00 = −r 11 = 1.…”
Section: Two Static Qubitsmentioning
confidence: 99%
“…In general, this proposal has shown that electron scattering based QIPs have a remarkable resilience, and they require a low level control over the spin interaction [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the involvement of the spatial degrees of freedom is a disadvantage of using electron scattering as an interaction channel between spins because it makes the scattering a non-unitary operation [19,28]. In order to create a unitary process, we need to implement a post-selection protocol, such as a spin polarization detection, and the possible implementations will be non-deterministic.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to study the conduction properties of crystals through the Kronig-Penney model [22] and Anderson localization in a disordered impurity array [23,24,25,26]. In a solid state quantum information scenario, δ-function potential barriers are used to depict the instantaneous interaction between a flying spin and a fixed magnetic impurity [27,28,29,30,31,32], to implement teleportation [33] and quantum memory [34].…”
Section: Introductionmentioning
confidence: 99%